Analysing Effect of Direction of Layups to Distortions of Laminated Carbon Fibre-Reinforced Composites - Dharu Feby Smaradhana (Mekanika: Majalah Ilmiah Mekanika, 2020)
The distortions of the laminates (flat panels and channel sections) with different stacking sequences were investigated in this lab session. There were two methods compared, measurement of the experimental specimens and prediction using classical laminate theory. The experimental results showed that the specimens with layup (90,03) and (03,90) had the largest curvature. The spring forward/back angles of the measurement was higher than those of the prediction though the trends of the distortions of the channel and the flat specimens were almost similar. There were several factors affecting distortions such as the tool thermal expansion, chemical shrinkage, the arrangement of vacuum bag and edge effects.